Effects of combined β-hydroxy-β-methylbutyrate (HMB) and whey protein ingestion on symptoms of eccentric exercise-induced muscle damage. Issue 1 (29th February 2016) - Shirato, Minayuki; Tsuchiya, Yosuke; Sato, Teruyuki; Hamano, Saki; Gushiken, Takeshi; Kimura, Naoto; Ochi, Eisuke
Abstract: Background: The purpose of this study was to examine the effects of combined β-hydroxy-β-methylbutyrate (HMB) and whey protein ingestion on muscle strength and damage following a single bout of eccentric exercise. Methods: Eighteen untrained male subjects were assigned to HMB and Whey protein (HMB + Whey; 3 g/day HMB and 36.6 g/day whey protein, n = 6), HMB (3 g/day, n = 6), or whey protein (36.6 g/day, n = 6) groups. Ingestion commenced 7 days before non-dominant elbow flexor eccentric exercise (30 deg/sec, 6 reps × 7 sets) and continued until 4 days post-exercise. The maximal isometric strength, muscle soreness, plasma creatine kinase (CK), lactate dehydrogenase (LDH) were assessed pre-exercise, and at 1, 2, 3, and 5 days after exercise. Results: The change scores of maximal isometric strength significantly decreased at day 1, 2, and 5 in the whey protein group compared to pre value and that in HMB + Whey protein and HMB groups decreased at day 1 and 5. The muscle soreness significantly increased in the whey and HMB + Whey protein groups at day 3 compared to pre value ( p < 0.05). CK and LDH significantly increased (time effect: p < 0.05) after exercise. However, all data were not significant difference among the groups. Conclusions: These results suggest that ingestion of combined HMB and whey protein does not have a role to inhibit muscle strength loss and soreness, and decrease in muscle damage markers after eccentric exercise in comparison with HMB and whey protein alone.